Ginsenoside Rg1-Notoginsenoside R1-Protocatechuic Aldehyde Reduces Atherosclerosis and Attenuates Low-Shear Stress-Induced Vascular Endothelial Cell Dysfunction - Zhang, Lei; Li, Yuan; Ma, Xin; Liu, Jiali; Wang, Xiaojie; Zhang, Lingxiao; Li, Chao; Li, Yunlun; Yang, Wenqing (Frontiers in Pharmacology, 2021)
Background: The Fufang Danshen formula is a clinically important anti-atherosclerotic preparation in traditional Chinese medicine. However, its anti-atherosclerotic effect is not well recognized, and the mechanisms of its combined active ingredients, namely Ginsenoside Rg1-Notoginsenoside R1-Protocatechuic aldehyde (RRP), remain unclear. The purpose of this study was to investigate the anti-atherosclerotic effects and potential mechanism of RRP in ApoE−/− mice and in low-shear stress-injured vascular endothelial cells. Methods: ApoE−/− mice were randomly divided into three groups: model group, rosuvastatin group, and RRP group, with C57BL/6J mice as the control group. Oil-red O, hematoxylin and eosin, Masson, and Movat staining were utilized for the observation of aortic plaque. Changes in the blood lipid indexes were observed with an automatic biochemistry analyzer. ET-1, eNOS, TXA2, and PGI2 levels were analyzed by enzyme-linked immunosorbent assay. In vitro, a fluid shear stress system was used to induce cell injury. Piezo1 expression in HUVECs was silenced using siRNA. Changes in morphology, proliferation, migration, and tube formation activity of cells were observed after RRP treatment. Quantitative Real-Time PCR and western blot analysis were employed to monitor mRNA and protein expression. Results: RRP treatment reduced the atherosclerotic area and lipid levels and improved endothelial function in ApoE−/− mice. RRP significantly repaired cell morphology, reduced excessive cell proliferation, and ameliorated migration and tube formation activity. In addition, RRP affected the FAK-PI3K/Akt signaling pathway. Importantly, Piezo1 silencing abolished the protective effects of RRP. Conclusion: RRP has anti-atherosclerotic effects and antagonizes endothelial cell damage via modulating the FAK-PI3K/Akt signaling pathway. Piezo1 is a possible target of RRP in the treatment of atherosclerosis. Thus, RRP has promising therapeutic potential and broad application prospect for atherosclerosis.